Friendship Formation and Mentalization in Children: A Qualitative Study - Mohammadi Bajgirani, Fatemeh-Alsadat; Golparvar, Mohsen; Bahramipour Isfahani, Mansoureh (Mental Health and Lifestyle Journal, 2026)
Stable and supportive friendships are of great importance for children’s growth and flourishing. The present study was conducted with the aim of developing a mentalization-based model of friendship formation in children, particularly rejected children. This study employed a qualitative design using a deductive thematic network analysis approach. The research context consisted of 100 scientific sources (including books, articles, and dissertations), and the sample included 33 scientific sources. A thematic analysis results recording form was used to extract the components of mentalization-based friendship formation. The textual data were analyzed through deductive thematic analysis (Attride-Stirling, 2001), along with the calculation of the Content Validity Index (CVI) and Content Validity Ratio (CVR). The findings indicated that the mentalization-based friendship formation model comprises four organizing themes: understanding one’s own experiences (mental, emotional, and behavioral) in friendship; understanding others’ experiences (mental, emotional, and behavioral) in friendship; co-mentalizing one’s own experiences (management and regulation of mental, emotional, and behavioral aspects) in friendship; and co-mentalizing others’ experiences (management and regulation of mental, emotional, and behavioral aspects) in friendship. Each of these four main themes also included a diverse range of subthemes. Based on the findings of this study on the mentalization-based friendship formation model, it is suggested that these results be utilized for the development and validation of mentalization-based friendship training programs and for constructing assessment tools to measure mentalization-based friendship capacity in children, in order to expand research in this field.